Harvard Data Science Review 2024
DOI: 10.1162/99608f92.141c99cf
|View full text |Cite
|
Sign up to set email alerts
|

Data Journeys in Popular Science: Producing Climate Change and COVID-19 Data Visualizations at Scientific American

Kathleen Gregory,
Laura Koesten,
Regina Schuster
et al.

Abstract: Vast amounts of (open) data are increasingly used to make arguments about crisis topics such as climate change and global pandemics. Data visualizations are central to bringing these viewpoints to broader publics.However, visualizations often conceal the many contexts involved in their production, ranging from decisions made in research labs about collecting and sharing data to choices made in editorial rooms about which data stories to tell. In this article, we examine how data visualizations about climate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The EE dimension enters the data journeys from the very beginning. As Gregory et al (2024) reported, Scientific American initially chose story ideas based on its staff members' interests and events in their personal lives, and then "Editors use their own emotional responses as an initial gauge to estimate the reception of a story." As a staff responded during a video conference interview conducted byGregory et al (2024), "There's the data, but there's an infinite number of stories we could tell […] If we have an emotional response, that's kind of the first level of oh, maybe this is something that people will also respond to."…”
Section: A Data Visualization Journey Starts With An Emotional Respon...mentioning
confidence: 99%
“…The EE dimension enters the data journeys from the very beginning. As Gregory et al (2024) reported, Scientific American initially chose story ideas based on its staff members' interests and events in their personal lives, and then "Editors use their own emotional responses as an initial gauge to estimate the reception of a story." As a staff responded during a video conference interview conducted byGregory et al (2024), "There's the data, but there's an infinite number of stories we could tell […] If we have an emotional response, that's kind of the first level of oh, maybe this is something that people will also respond to."…”
Section: A Data Visualization Journey Starts With An Emotional Respon...mentioning
confidence: 99%